ANALISIS FAKTOR KESULITAN SISWA DALAM MEMBACA UNTUK PERMULAAN DI KELAS I SDN 89 PALEMBANG - Arinda Risanti; A. Heryanto; Sunedi Sudarman (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research aims to understand the analysis of students' difficulties in reading at the beginning level in Grade 1 of SDN 89 Palembang. Based on observation results, there are difficulties encountered by students in reading at the beginner level in Grade 1 of SD Negeri 89 Palembang. The research is descriptive and qualitative, utilizing data analysis techniques involving data reduction, data presentation, and data collection methods such as observation, interviews, and documentation. The research findings indicate that there are factors contributing to students' difficulties in reading at the beginner level in Grade 1 of SDN 89 Palembang. Students face challenges in initial reading, influenced by two main factors: the students themselves and their parents. The difficulties encountered in the beginner reading of Grade 1 students at SDN 89 Palembang include struggles in recognizing vowel and consonant letters, distinguishing words with the same initial letters, identifying words with the same initial syllables, and forming words from individual components.